Dietary nucleotides can prevent glucocorticoid-induced telomere attrition in a fast-growing wild vertebrate - Casagrande Stefania; Loveland Jasmine L.; Oefele Marlene; Boner Winnie; Lupi Sara; Stier Antoine; Hau Michaela (WILEY, 2025)
Telomeres are chromosome protectors that shorten during eukaryotic cell replication and in stressful conditions. Developing individuals are susceptible to telomere erosion when their growth is fast and resources are limited. This is critical because the rate of telomere attrition in early life is linked to health and life span of adults. The metabolic telomere attrition hypothesis (MeTA) suggests that telomere dynamics can respond to biochemical signals conveying information about the organism's energetic state. Among these signals are glucocorticoids, hormones that promote catabolic processes, potentially impairing costly telomere maintenance, and nucleotides, which activate anabolic pathways through the cellular enzyme target of rapamycin (TOR), thus preventing telomere attrition. During the energetically demanding growth phase, the regulation of telomeres in response to two contrasting signals - one promoting telomere maintenance and the other attrition - provides an ideal experimental setting to test the MeTA. We studied nestlings of a rapidly developing free-living passerine, the great tit (Parus major), that either received glucocorticoids (Cort-chicks), nucleotides (Nuc-chicks) or a combination of both (NucCort-chicks), comparing these with controls (Cnt-chicks). As expected, Cort-chicks showed telomere attrition, while NucCort- and Nuc-chicks did not. NucCort-chicks was the only group showing increased expression of a proxy for TOR activation (the gene TELO2), of mitochondrial enzymes linked to ATP production (cytochrome oxidase and ATP-synthase) and a higher efficiency in aerobically producing ATP. NucCort-chicks had also a higher expression of telomere maintenance genes (shelterin protein TERF2 and telomerase TERT) and of enzymatic antioxidant genes (glutathione peroxidase and superoxide dismutase). The findings show that nucleotide availability is crucial for preventing telomere erosion during fast growth in stressful environments.